Career Anchors Reimagined: Expertise, Stability and Recognition in Structured Organizational Fields - Simionca Anca Simona (Studia Universitatis Babes-Bolyai Sociologia)
This article explores how professionals in a multinational IT company construct career identities that intertwine ambition, recognition, and stability—challenging dominant models that equate ambition with autonomy and instability. Drawing on a sequential exploratory mixed-methods design—48 qualitative interviews and a survey of 764 employees—it identifies “expertise” as a distinct career anchor defined not merely by technical skill, but by internal recognition, symbolic legitimacy, and trusted authority. Quantitative validation through factor analysis confirmed a revised nine-anchor model, with widespread hybrid identities (e.g., expertise + lifestyle, expertise + security) emerging as normative, not transitional. The article reframes security not as passivity but as an entitlement earned through excellence. Interpreted through a career field and habitus lens, these findings reposition career anchors as relational identity positions shaped by organizational recognition regimes, symbolic capital, and contextual fit. The study contributes a grounded critique of protean and boundaryless career models, proposing an alternative understanding of stability, ambition, and growth in contemporary structured work environments.